The Analysis on Syndromes Involving Cough by Application of Six Channels Syndrome Differentiation Pattern - Fazlie, Mohd Sani Lim (2015)
Objectives: Coughs are among the most common symptoms seen during clinical practice. For the purpose of seeking a better treatment methodology for treating syndromes involving cough, the theory of Six Channels Syndrome Differentiation Pattern is studied and applied.